PENGARUH GREEN MARKETING DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK GARNIER (Studi Kasus Pada Konsumen Toko LOVA di Kota Bengkulu) - Silvi Ardila; Mardhiyah Dwi Ilhami (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to determine the influence of green marketing and brand image on the purchase decisions of Garnier products among consumers at LOVA Store in Bengkulu City. This research is a descriptive quantitative study. The population in this study consists of consumers who purchase Garnier products at LOVA Store. Data collection techniques used include observation, interviews, and questionnaires. Data analysis techniques involve descriptive analysis, inferential analysis using SPSS, and the coefficient of determination analysis (R²). The results show that green marketing has a positive influence on consumer purchase decisions. This means that the better the green marketing strategies implemented, the higher the tendency of consumers to make purchases. Brand image also has a positive effect on purchase decisions. The better the brand image formed in the minds of consumers, the more likely they are to choose and buy Garnier products. Simultaneously, green marketing and brand image have a positive and significant influence on purchase decisions. This indicates that implementing environmentally friendly marketing strategies and maintaining a consistent brand image can enhance consumer purchase decisions for Garnier products. Keywords: Green marketing, brand image, purchase decision, Garnier, Bengkulu City